Analisis Kepatuhan Pajak Pekerja Muda Indonesia dengan Pendekatan Motivational Posture Theory - Utomo, Priandaru Wahyu; Nugroho, Rahadi; Cahyani, Galuh Dwi (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to analyze the tax compliance of the younger generation in Indonesia using the Motivational Posture Theory approach.Methodology/Approach: The study was conducted by distributing an online questionnaire to prospective respondents through various channels and analyzed using linear regression.Results/Findings: The results show that the postures of commitment, capitulation, disengagement, and game playing significantly influence the tax compliance of young workers in Indonesia, while the posture of resistance has no significant impact on tax compliance among young workers in Indonesia.Conclusions: This study shows that in the context of tax compliance of young workers in Indonesia, the motivational postures of commitment and capitulation play an important role in increasing tax compliance, while disengagement and game playing actually decrease tax compliance. Commitment, which reflects trust in the tax system, and capitulation, which reflects recognition of the tax authority, have a significant positive impact on tax compliance. Conversely, disengagement, which reflects the psychological separation of taxpayers from the tax authority, and game playing, which reflects efforts to find loopholes to avoid taxes, contribute to decreasing tax compliance. Limitations: The distribution of the online questionnaire through various channels needs to be followed up with approaches to different young worker communities in order to obtain a larger and more representative sample.Contribution: Research on tax compliance among the younger generation is still very rare in Indonesia, so this study provides some insights into the tax compliance of the younger generation.